Produção de kombucha e caracterização do seu potencial bioativo - Bitencourt, Ligia (2022)
The search for healthier lifestyles has become popular in recent times. With this, there was the popularization of the kombucha drink, a sweet fermented liquid based on green tea and/or black tea, mainly. The objective of this work is the production and characterization of kombucha from the best fermentative condition, literature data and previous tests. The characterization of the fermented liquid was carried out in relation to bioactivity (antioxidant potential, using the DPPH method and phenolic compounds, using the Folin-Ciocalteu method) aiming at future cosmetic applications. In the test of phenolic compounds we obtained results of 213,324 mgEAG/mL, which are in agreement and also above the literature, being able to make adjustments so that its result can be the best possible. As for the DPPH test, we obtained values from 54.91% to 91.29%, also according to the literature. Therefore, it is demonstrated that kombucha is a bioactive ingredient with potential for the production of cosmetics, especially with antioxidant potential.